Age at Diagnosis and Breast Cancer Survival in Iran. (22nd November 2012) - Vostakolaei, Fatemeh Asadzadeh; Broeders, Mireille J. M.; Rostami, Nematollah; van Dijck, Jos A. A. M.; Feuth, Ton; Kiemeney, Lambertus A. L. M.; Verbeek, André L. M.
Abstract : Background . Tumour characteristics are the most important prognostic factors in breast cancer. Patient-related factors such as young age at diagnosis, obesity, and smoking behaviour may also modify disease outcome. Due to the absence of a unique definition for "young age breast cancer" and the resulting variation in disease management, findings on the association between young age and prognosis of breast cancer are controversial. Methods . This study included 1500 patients with a primary diagnosis of breast cancer in six Iranian hospitals from 5 provinces. We modelled the relative excess risk (RER) of breast cancer death to age at diagnosis and tumour characteristics. Results . Excess risks of death were observed for stage IV disease and poorly differentiated tumours: RER of 4.3 (95% CI: 1.05–17.65) and 3.4 (95% CI: 1.17–9.87), respectively. "Older" patients, particularly those aged 50 and over, presented more often with advanced and poorly differentiated tumours (P = 0.001 ). After adjustment for stage, histological grade, Her-2 expression, estrogen and progesterone receptors, and place of residency, breast cancer mortality was not significantly different across age groups. Conclusion . We conclude that there is no prognostic effect of age at diagnosis of breast cancer among breast cancer patients treated at cancer centres in different parts of Iran; young and relatively old women have similar risks of dying from breast cancer.